Technology-based business opportunity identification in a Latin American country - Arechavala-Vargas, Ricardo; Núñez-López, Viridiana; Madrigal-Torres, Berta E. (Acta Universitaria, 2019)
In recent years, the number and quality of entrepreneurial projects that pursue technology-based business opportunities in Latin America, specifically in Mexico, have been growing. To support such efforts, it is important to understand the process through which entrepreneurs discover and create a technology-based business opportunity with the available resources as well as its similarities and differences regarding those processes in industrialized economies. This research analyzes technology-based business opportunity identification processes in Mexico and compares it with what is reported in the specialized literature about such processes in industrialized economies. The findings are based on content analysis of eight in-depth interviews applied to technology-based entrepreneurs. Specific contributions are discussed for the analysis of the Latin American innovation ecosystems and to the available theory about technological business opportunity identification processes. The main contribution to the specialized literature is the identification of patterns in the technology-based opportunity discovery process in contexts where knowledge resources and infrastructure are less abundant than in industrialized economies. The results illustrate the importance of the processes and skills that technology entrepreneurs must deploy to gain knowledge they know exists and those they need to master in order to take advantage of knowledge-based economic opportunities.